Research on the strength of selective laser sintering core. Issue 1 (1st September 2022) - Li, Jiuru; Qu, Jiuhe; Chen, Juhui; Zhou, Haitian; Sun, Yongguo; Fu, Lin
Abstract: Taking the tensile strength as the inspection index, the single-factor influence experiment was carried out on the addition of phenolic resin and the four factors of laser power, laser scanning rate and sand thickness in the sintering process, and the optimal level combination of each factor was obtained: the addition of phenolic resin. 5%, laser power 38W, laser scanning rate 3400mm/s, sand thickness 0.25mm.